The effect of intracuff alkalinized 2% lidocaine on emergence coughing, sore throat, and hoarseness in smokers - Navarro, Laís Helena Camacho [UNESP]; Lima, Rodrigo Moreira e [UNESP]; Aguiar, Andressa Simões; Braz, José Reinaldo Cerqueira [UNESP]; Carness, Jeffrey M.; Módolo, Norma Sueli Pinheiro [UNESP] (Associação Médica Brasileira, 2012)
OBJECTIVE: We evaluated whether endotracheal tube (ETT) intracuff alkalinized lidocaine was superior to saline in blunting emergence coughing, postoperative sore throat, and hoarseness in smokers. METHODS: In our prospective, double-blind trial, we enrolled 50 smoking patients undergoing surgery under general anesthesia including nitrous oxide (N2O). Patients were randomly allocated to receive either ETT intracuff 2% lidocaine plus 8.4% sodium bicarbonate (L group), or ETT intracuff 0.9% saline (S group). The ETT cuff was inflated to achieve a cuff pressure that prevented air leak during positive pressure ventilation. Incidence of emergence coughing, sore throat, and hoarseness were analyzed. The volume of inflation solution, the intracuff pressure, the duration of anesthesia, the time elapsed to extubation after discontinuation of anesthesia, and the volume of the inflation solution and the air withdrawn from the ETT cuff were also recorded. RESULTS: Intracuff alkalinized 2% lidocaine was superior to saline in blunting emergence coughing (p < 0.001). The incidence of sore throat was significantly lower in the L group at the post-anesthesia care unit (PACU) (p = 0.02). However, at 24 hours after extubation, sore throat incidence was similar in both groups (p = 0.07). Incidence of hoarseness was similar in both groups. Intracuff pressure in the saline group increased with time while the intracuff pressure in the lidocaine group remained constant. CONCLUSION: The present study demonstrated that the intracuff alkalinized 2% lidocaine was superior to saline in decreasing the incidence of emergence coughing and sore throat during the postoperative period in smokers.
Keywords: Smoking; lidocaine; cough; hoarseness; nitrous oxide